2022
DOI: 10.3390/foods11213357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bioactive Compounds, and Physicochemical and Sensory Properties of Gluten-Free Muffins Enriched with Persimmon ‘Rojo Brillante’ Flour

Abstract: Because of the nutritional need of patients with celiac disease, producing quality gluten-free diet food is important. This study evaluated the use of persimmon flour on the properties of muffins. Persimmon flour obtained from the astringent variety ‘Rojo Brillante’, which is often discarded due to its characteristic astringency, was added to muffins replacing corn flour (10%, 20%, and 30%). Despite the height differences between the control muffin and the muffins with persimmon flour, similar mechanical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…These authors explained that this fact was due to partial sugar caramelization. Along the same lines, after adding persimmon powder to gluten-free muffins, Hosseininejad et al [10] reported an increase in sweetness, a fruity and caramel taste, and a dark color as the main sensory changes compared to the control sample with no added powder.…”
Section: Consumer Interest In Each Persimmon-derived Product Acceptan...mentioning
confidence: 89%
See 2 more Smart Citations
“…These authors explained that this fact was due to partial sugar caramelization. Along the same lines, after adding persimmon powder to gluten-free muffins, Hosseininejad et al [10] reported an increase in sweetness, a fruity and caramel taste, and a dark color as the main sensory changes compared to the control sample with no added powder.…”
Section: Consumer Interest In Each Persimmon-derived Product Acceptan...mentioning
confidence: 89%
“…In a recent review about the influences of dried fruit and vegetable powder on cake quality, Perfilova et al [24] reported that the powder of fruits and vegetables exhibited benefits in attracting consumers by improving the appearance, texture, nutritional values, sensorial properties and shelf life of cakes. Specifically for persimmon powder, Hosseininejad et al [10] reported that its addition acted as a functional ingredient to glutenfree muffins. These authors used persimmon powder to partially replace corn flour and described an increase in carotenoids and antioxidant capacity.…”
Section: Consumption Contexts For Fresh Fruit and Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The STC was determined in the ethanolic extract according to the methodology described by Hosseininejad et al . (2022b). The results were expressed in dry basis as g of gallic acid equivalent (GAE)/100 g db.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to their ingredients (wheat flour, sugar, fat, eggs), muffins are considered high-calorie sweet products. Currently, people are becoming more conscious of health and nutrition, so it is important to enhance these types of products with valuable ingredients to make them healthier [ 15 ]. In recent years, several studies have proven that blackberries can be an excellent functional food ingredient due to their bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%